Breaking ElGammal encryption of two different mesagges

I'm stuck with the following problem on ElGammal encryption.

We work on $\mathbb{Z}_{p}^*$ where $p$ is prime and we are given $p$, the generator $g$ of $\mathbb{Z}_{p}^*$ , the public key used $y$ and five encryptions $(u_1,v_1), \cdots, (u_5,v_5)$ where each of them is a encryption of a message $m$ that can be $1$ or $-1$.

Please refer to the second scheme of this question if you need more details on the ElGammal cryptosystem I'm using.

As a hint I'm told to look for a subgroup of index two. I tried to solve the discrete logarithm problem in that subgroup with sage but as this post discusses the complexity is only reduced by a constant so that it is still intractable.

I give you the code I was using in case you have some comments.

F = Integers(p)
gmod = F(g)
q = p // 2
F2 = Integers(q)
gmod2 = F2(g)
ymod2 = F2(y)
gmod2 = F2(g)
ymod2 = F2(y)

Can you figure out how this could be solved?

Edit:

In my case $\frac{p-1}{2}$ is already prime.

• Hint: we know that (for any $1 \le z < p$, we have $z^{p-1} \equiv 1$ (Fermat's Little Thereom); $z^{p-1} = (z^q)^2$; and so we know that, whatever $z^q$ is, when squared, it gives us 1. Given that $p$ is prime, what are the possible squareroots of 1? Does that give you a hint what $(y^r)^q$ could be? Nov 1 '16 at 17:58

Further hint: suppose we computed $q = (p-1)/2^\lambda$ odd, and given $(u_1, v_1) = (g^r, m y^r)$, we compute $(g^r)^q, (m y^r)^q$. Once we have done that, how can you distinguish the $m=1$ and $m= -1$ cases?

Thanks to poncho's hints we can work as follows:

1.Compute $(g^r)^q$. I claim that:

$(g^r)^q = \begin{cases} 1 &\quad\text{if r is even}\\ \neq 1 &\quad\text{if r is odd} \ \end{cases}$

For the first case we have $(g^{r})^{\frac{p-1}{2}} = (g^{p-1})^{\frac{r}{2}} = 1$. For the second case, the result was one then $ord(g) = p-1$ divides $r \frac{p-1}{2}$. However, $p-1$ is even and we assumed that $r$ and $\frac{p-1}{2}$ are odd numbers. An even number cannot divide an odd one.

2.Compute $(my^r)^q = m^q y^{rq} = m y^{rq}$ where we used that $m \in \{-1,1\}$.

3.Compute $y^{rq}$. I claim that (assume x is the private key of the algorithm):

$y^{rq} = \begin{cases} 1 &\quad\text{if (r is even) or (r is odd and x is even)}\\ -1 &\quad\text{if r is odd and x is odd} \ \end{cases}$

If r is even we can reason as we did in the first case. Assume r is odd. Then $(y^{rq})^2 = y^{2rq} = 1$ and as $\mathbb{Z}_p$ is a field we know that this equation has at most 2 solutions, namely -1 and 1.

If assume that $y^{rq} = 1$ then by definition of $y$ we get $y^{rq} = g^{xrq} = 1$ so that $ord(g) = p-1$ divides $xr \frac{p-1}{2}$. Here $r$ and $\frac{p-1}{2}$ are odd numbers (in my edit I specified that $\frac{p-1}{2}$ was prime) so that necessarily $x$ must be even. Therefore, if we now assume that $y^{rq} = g^{xrq} = -1$, $x$ needs to be odd.

4.Compute $y^q = g^{xq}$ so that as in the first case you'll get:

$g^{xq} = \begin{cases} 1 &\quad\text{if x is even}\\ \neq 1 &\quad\text{if x is odd} \ \end{cases}$

Let's wrap up. We can decide if $x,r$ are odd or even. This implies we can decide if $y^{rq}$ is 1 or -1 and this implies that we can decide if $(my^r)^q$ is m or -m.